Information Sharing Between Retailers and International Manufacturers : A Case Study of the Automobile Market in Luleå - Lindqvist, Robin; Malm Helgesson, Carl (2016)
The globalization has contributed to companies constantly searching to find new opportunities to increase the efficiency of their operations. Through this arises international collaborations that may be referred to as global supply chains. Providing the necessary aspects of controlling a large supply chain that stretches across several borders are communication, which is considered to be a key factor to bind the different parts together, to create a functional and efficient supply chain. The purpose of this thesis is to provide a better understanding of how the information flow is used to have a more efficient automobile retail market.For this thesis a case study was chosen and interviews with five brand managers at different automobile retail stores in Luleå are the foundation of the empirical data. The data suggest that retailers are of great benefit with increased information flow to their manufacturer, retailers are affected by the market structure in Luleå, which does not correlate with the theory, which states that the automobile market are horizontal. Information exchange between the retailers and manufacturers are in constant flow, objecting to not having any misunderstandings or delays of information. As the automobile industry are of global scale the data shows an constant development of information flow, ever changing and adapting to a market that is constantly changing. The information flow are of great importance to how great the “Bullwhip effect” may have, real-time data and total information sharing to manufacturer, are two of the aspects that this study have found to are used to reduce it. Validerat; 20160617 (global_studentproject_submitter)